Clostridium perfringens bacteremia associated with colorectal cancer in an elderly woman - Huang, Chia-Yu; Wang, Mu-Cyun (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Huang CY, Wang MC. Clostridium perfringens bacteremia associated with colorectal cancer in an elderly woman. Turk J Gastroenterol 2020; 31(12): 960-1.